3D Mimicry of Native‐Tissue‐Fiber Architecture Guides Tendon‐Derived Cells and Adipose Stem Cells into Artificial Tendon Constructs. Issue 31 (20th June 2017) - Laranjeira, Mariana; Domingues, Rui M. A.; Costa‐Almeida, Raquel; Reis, Rui L.; Gomes, Manuela E.
Abstract : Tendon and ligament (T/L) function is intrinsically related with their unique hierarchically and anisotropically organized extracellular matrix. Their natural healing capacity is, however, limited. Here, continuous and aligned electrospun nanofiber threads (CANT) based on synthetic/natural polymer blends mechanically reinforced with cellulose nanocrystals are produced to replicate the nanoscale collagen fibrils grouped into microscale collagen fibers that compose the native T/L. CANT are then incrementally assembled into 3D hierarchical scaffolds, resulting in woven constructions, which simultaneously mimic T/L nano‐to‐macro architecture, nanotopography, and nonlinear biomechanical behavior. Biological performance is assessed using human‐tendon‐derived cells (hTDCs) and human adipose stem cells (hASCs). Scaffolds nanotopography and microstructure induce a high cytoskeleton elongation and anisotropic organization typical of tendon tissues. Moreover, the expression of tendon‐related markers (Collagen types I and III, Tenascin‐C, and Scleraxis) by both cell types, and the similarities observed on their expression patterns over time suggest that the developed scaffolds not only prevent the phenotypic drift of hTDCs, but also trigger tenogenic differentiation of hASCs. Overall, these results demonstrate a feasible approach for the scalable production of 3D hierarchical scaffolds that exhibit key structural and biomechanical properties, which can be advantageously explored in acellular and cellular T/L TE strategies. Abstract : Advanced 3D textile scaffolds are fabricated by applying rational construction designs to mimic key functional features of native tendons/ligaments. Their unique nano‐to‐macro 3D hierarchical architecture prevents the phenotypic drift of human‐tendon‐derived cells, and triggers the tenogenic differentiation of human adipose stem cells without biochemical supplementation, demonstrated to be a noble solution for engineering these highly specialized, load‐bearing, anisotropic tissues.